Serbia: New Higher Education Strategy - Uvalic-Trumbic, Stamenka (International Higher Education, 2012)
A new higher education strategy is being developed in Serbia as part of a wider reform of education. Boosting enrolments, promoting both the non-university sector on one end and excellence on the other, strengthening relevance and quality and rationalizing the university network are the basis of this strategy.